2019
DOI: 10.1016/j.envpol.2019.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disrupting effects of tebuconazole on different life stages of zebrafish (Danio rerio)

Abstract: Tebuconazole is a widely used fungicide that has been detected in water ecosystems, of which the concentrations may affect the endocrine function of aquatic organisms. At present study, tissue-specific bioaccumulation of tebuconazole was found in ovary of adult zebrafish, indicating a potential risk of endocrine disruption. In order to evaluate the potential endocrine disrupting effects, three life stages (2 hpf (hours post-fertilization) À60 dpf (days post-fertilization), Stage I; 60e120 dpf, Stage II; 180e20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 46 publications
2
27
1
1
Order By: Relevance
“…Abnormal gonadal development, including promotion or retardation of developmental processes, not only causes disease, but also causes inter‐generational effects (Tokumoto et al, ). It was shown that TEB bio‐accumulated significantly more in the gonads than in other tissues (except liver) and gonadosomatic index (GSI) values (gonad weight/body weight × 100) significantly reduced after exposure to TEB in adolescence male and female zebrafish, indicating that TEB disrupted gonadal development (Li et al, ). Consistent with that study, TEB exposure retarded gonadal development in C.elegans , as shown by a dose‐dependent increase in the number of worms that remained in larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal gonadal development, including promotion or retardation of developmental processes, not only causes disease, but also causes inter‐generational effects (Tokumoto et al, ). It was shown that TEB bio‐accumulated significantly more in the gonads than in other tissues (except liver) and gonadosomatic index (GSI) values (gonad weight/body weight × 100) significantly reduced after exposure to TEB in adolescence male and female zebrafish, indicating that TEB disrupted gonadal development (Li et al, ). Consistent with that study, TEB exposure retarded gonadal development in C.elegans , as shown by a dose‐dependent increase in the number of worms that remained in larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…The tebuconazole is known to have thyroid disrupting potential (Liang et al, 2015; Li et al, 2019). The TBG binds with thyroid hormones and play important roles in the circulation of thyroid hormones (Chakravarthy & Ejaz, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, 2.1 to 15.5 pg of tebuconazole in 1 mg of hair has been reported during occupational and environmental exposure (Mercadante et al, 2018; USEPA, 2020). The endocrine disruption of tebuconazole was found with the concentrations at 0.05, 0.20, and 0.50 mg/L in zebrafish (Li et al, 2019). In addition, exposure of 0.20 and 0.50 mg/L tebuconazole reduces thyroxine and triiodothyronine in F0 generation of zebrafish (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite of TiO2 and SnO2 QDs may prove to be beneficial for efficient decomposition of Endocrine Disrupting Chemicals (EDCs). Exposure to EDCs in nature is a basic worry with unclear long-term negative impacts [12][13][14][15][16][17][18][19][20][21]. EDCs are discharged into nature by people, animals and industry; and therefore, enters in bodies through soil, surface water and ground water.…”
Section: Introductionmentioning
confidence: 99%